Implementation of Edu-Digital Websites and Local Food Interventions: Efforts to Improve Community Knowledge and Skills in Overcoming Stunting in Sari Murni Village, Pohuwato District - Lilan Dama; Chairunnisa Lamangantjo; Muh. Nur Akbar; Margaretha Solang; Budi Santosa; Lisa Djafar; Firdausi Ramadhani; Muhammad Jihad Firman (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
There is a high incidence of stunting in various villages across Indonesia these days. One of the reasons these problems are difficult to solve is the lack of knowledge and understanding by the community. The goal of the local food edu-digital website implementation program is to increase community knowledge of stunting and the use of local foods that can help overcome stunting in Sari Murni Village, Pohuwato Regency, Gorontalo Province. In this service program, three activities are carried out: 1) data collection for website content, 2) creation of local food edu-digital websites, and 3) website management training. Through this activity, we obtained (1) digital documentation consisting of text, images, and videos, and (2) an information sistem containing information about stunting, local food potential which can be overcome stunting, and local food processing methods, in addition to village information about development and activities.